2021
DOI: 10.1007/s11270-021-05473-w
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Heavy Metal Accumulations in Plant Organs and Soil White Birch (Betula verrucosa Ehrh.) Plantation

Abstract: birch barks as a biomonitoring tool may be useful, particularly in monitoring increases in Cd concentrations in urban settings. Additionally, to maximize heavy metal retention, it is advised to use hyperaccumulator plant combinations according to local climatic conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Last research has shown that B. pendula has developed traits, which help to survive [ 48 ]. For this reason, it is used as a remedial plant [ 49 51 ], which makes it more and more widespread and conducive to use in biomonitoring [ 1 , 51 , 52 ]. Therefore, it becomes important to determine the influence of the soil species, as well as other physicochemical properties of the soil on the possibility of accumulation of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Last research has shown that B. pendula has developed traits, which help to survive [ 48 ]. For this reason, it is used as a remedial plant [ 49 51 ], which makes it more and more widespread and conducive to use in biomonitoring [ 1 , 51 , 52 ]. Therefore, it becomes important to determine the influence of the soil species, as well as other physicochemical properties of the soil on the possibility of accumulation of heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metals present in the environment can be of natural origin (weathering of rocks, volcanic eruptions) or anthropogenic. In the environment, they are a natural component of the earth's crust; however, diverse types of anthropogenic activity lead to disturbance in geochemical cycles, resulting in the accumulation of metal in relation to background levels [ 1 3 ]. Soil heavy metal pollution can come from a variety of sources, both natural sources and anthropogenic ones such as industry, fertilization, etc.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations